Educação estatística no contexto da educação crítica - Campos, Celso Ribeiro; Jacobini, Otávio Roberto; Wodewotzki, Maria Lucia L [UNESP]; Ferreira, Denise H L (My University, 2011)
This article deals with the development of three competencies defined and studied in the context of Statistics Education (literacy, thinking and statistical reasoning). These competencies based on interpretation and understanding of critical information from real data are associated with an education geared toward the formation of critical citizenship and are in agreement with the principles that guide Critical Education. In this context, we consider Mathematical Modeling as a concrete possibility for integration between Critical Education and Education Statistics. We show that work with modeling projects in the classroom takes place in a context in which teaching is guided by the fundamentals of Critical Education. We present a project entitled Teaching Statistics and the financial market which illustrates the congruence between the objectives of Education Statistics and Critical Education.
Statistics education in the context of Critical Education
Keywords: Competencies; Critical education; Modeling projects; Statistics education